Propuesta: Creación de una Oficina de Apoyo para la Administración de Proyectos en ABC Software - León-Méndez, Patricia; Lobo-Caamaño, Susana (Instituto Tecnológico de Costa Rica, 2012)
The project management, following the procedures recommended by the Project Management Institute (PMI®), is a requirement to ensure successful administration and greater achievement of the strategic objectives of the company. For this reason, the idea of putting this project on paper comes out. It aims to present a proposal for creating an office to support the management of projects at ABC Software, which allows the achievement of the desired level of excellence. This project was done through applied research, which aims to find a practical solution to a problem. The diagnosis of the maturity level of the company, in relation to “Project Management,” demonstrated that the company is in a "medium” level. This information, in conjunction with the documentation and literature reviewed, and the expert judgment, determined the type of office to be implemented; as well as its characteristics according to the current needs identified in the company. The main recommendations of this study were designed to foster the implementation of the proposal, intended for the company to take advantage of the benefits provided by this type of office. As a result, it will be able to achieve an improvement in the management of their projects, providing the best quality to their customers with an improved performance of return on investment.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2012.
Keywords: Gestión de proyectos; Administración; Inversiones; Calidad; Servicio al cliente